Antigua and Barbuda. Significant achievements 2019 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The main activities carried out by the Institute in Antigua and Barbuda during 2019 are identified, with respect to the needs and interests of the country, strengthening issues of sustainable development, economic development, local development, rural agriculture, financing, governance and health and safety of food. Likewise, work was done on resilience to climate change, through the construction of a hydroponic unit, pest control was addressed, especially in the management of Giant African Snails (GAS) and the citrus aging disease. Finally, support was provided to highlight the production and marketing of local products.